Manufacturing information & data systems analysis, design & practice - Cecelja, Franjo (Penton, 2002)
Recent years have witnessed an increase in the use of information technology in manufacturing, so much so that it has rapidly permeated the organization at every level. Consequently, there is a growing need for those related to or interested in manufacturing to understand the nature of this technology and the way it can best be used to increase competitive advantage, hence the profit. This book is a contribution towards better understanding of information technology and information systems and their application in manufacturing. The main feature of this book is that it addresses information systems and its application in manufacturing with a view to improving the competitive advantage. It offers fundamental understanding of information technology and underpinning principles, but also practical issues related to its implementation and operation. Additionally, the material is structured such that the reader is taken logically from basic principles to practical issues of information systems. Yet, chapters tend to be sufficiently independent making the text suitable for those with particular interest.
Keywords: Manufacturing processes -- Data processing.; Industrialists -- Information resources management.; Industrial management -- Data processing.; Management information systems.; elektronické knihy; electronic books